Beyond Symbolic Recognition: Constitutional Reform for Indigenous Peoples’ Rights in Indonesia’s Plural Democracy - Andry Wikra Wardhana Mamonto; Yosia Hetharie (ARTES LIBRES INSTITUTUM, 2025)
This research examines the limits of Indonesia’s constitutional recognition of indigenous peoples and proposes a reform agenda to move beyond symbolic acknowledgment toward substantive constitutional guarantees. The study is motivated by the enduring gap between Article 18B(2) of the 1945 Constitution, which conditionally recognizes “masyarakat hukum adat,” and the lived reality of indigenous communities who continue to experience dispossession, marginalization, and exclusion from decision-making processes. The objective is to assess why recognition remains symbolic and how constitutional reform can ensure enforceable rights consistent with democratic pluralism and global normative standards. Employing a normative legal research method, the study combines statutory, doctrinal, and jurisprudential analysis with comparative constitutional approaches and conceptual frameworks of constitutionalism, multicultural citizenship, and recognition theory. It draws upon global experiences, particularly from Latin America, Canada, and New Zealand, where constitutional reforms have embedded indigenous rights as substantive guarantees through plurinational frameworks, fiduciary obligations, and institutionalized legal pluralism. The results demonstrate that Indonesia’s recognition remains conditional, fragmented, and weakly institutionalized, rendering it ineffective in protecting indigenous peoples’ rights. In contrast, comparative models illustrate that recognition must be unconditional, operationalized through independent institutions, and grounded in legal pluralism. The findings suggest that sustainable reform in Indonesia requires rearticulating constitutional language, establishing an independent commission on indigenous rights, strengthening judicial enforcement, integrating indigenous legal systems, and linking recognition to environmental stewardship and democratic participation. Ultimately, this research contributes to global debates on indigenous constitutionalism by offering a prescriptive model for reform that positions Indonesia to embody its constitutional motto of “unity in diversity” in both principle and practice.